DALAM WAKTU 25 – 30 TAHUN LAGI SELURUH UMAT MANUSIA AKAN BERSATU PERSPEKTIF SPIRITUAL (SEBUAH RENUNGAN) - Yupardhi, W. Sayang (Institut Hindu Dharma Denpasar, 2019)
Until now where ever in the world, unity is no show yet it eternal identity, so friction occurs at some countries that marking with various violent among sesame due to self beneficial (excessivenees of ego). This is the ?Kali? personality qualification that sink in ocean of sin where it?s not human eternal character that occupaid their selve. Hanuman who already unity with Rama ?Avatar? is eternal association that can be catagorised could reach everything are need (not desire). This would inspire human being of modern time through unity among sesame in which could realized unity in diversity physicaly and non physicaly i.e. Soul. The essiest way to form unity is to lern to implement God principles in all of His creations properly. The value that already inheritance by Indonesian Freedom Country must be understood accordingly in order to own togather in supervicing unity to form Indonesian character building. Upanishad teachs that unity is the key of success to reduce the ocean suffer in this live, so if all people want to share in different society they would be have high credit in order to do pray and chanting ?Om? (primordial voiceof the God). This tend to insure firm pice and stability in each country follows directions and implementation of basic gathering in unity.The unity of all human being (Hindu, Christiany, Budha, Islam, etc) was said by holy man that they can fill it latter within 25 ? 30 years.